Analysis Of Iron (Fe) And Zinc Content (Zn) From Bay Leaves (Syzygium Polyanthum) - Rhisma Mutiara Devi; Adi Magna Patriadi Nuhriawangsa; Setyo Sri Rahardjo (International Journal of Health and Pharmaceutical (IJHP), 2024)
Background: Anemia is a nutritional problem in children, pregnant women, teenagers, and women of childbearing age. The prevalence of anemia in Indonesia in 2018 among young women was 48.9%. Bay leaves are widely known in various culinary and traditional medicine in Indonesia. Objective: This study analyzes the iron (Fe) and zinc (Zn) content in bay leaves (Syzygium polyanthum) growing in Karanganyar, Indonesia. Method: This research is an observational descriptive experiment with a laboratory approach carried out through a series of experiments. An Atomic Absorption Spectrophotometer (AAS) is used to analyze iron levels. Results: This research shows that the average concentration of Fe in bay leaves growing in Karanganyar is 294.28 mg/L per 100 grams of bay leaves. Meanwhile, the average concentration of Zn in bay leaves is 15.19 mg/L per 100 grams of bay leaves. According to TKPI 2017, bay leaves contain around 44.1 mg of iron per 100 g. Apart from that, the results of research conducted by Suharni 2021 show that 100 g of bay leaf extract contains around 30.09 mg of iron. Comparison with other plants shows that bay leaves contain much more iron and zinc. Higher than plants such as Moringa leaves. As an example of another plant that is often consumed, Moringa leaves have a lower iron and zinc content, namely 6 mg Fe/100 grams of Moringa leaves and 0.6mg/100 grams of zinc. In addition, this research opens up opportunities for application to experimental animals such as mice, which can be given bay leaf powder to understand its impact on iron and zinc levels in their bodies. Conclusion: The average test concentration of Fe in bay leaves is 294.28 mg/L. Meanwhile, the average concentration of Zn in bay leaves is 15.19 mg/L.